Data privacy management and autonomous spontaneous security 5th International Workshop, DPM 2010 and 3rd International Workshop, SETOP 2010, Athens, Greece, September 23, 2010, Revised Selected Papers - Garcia-Alfaro, Joaquin; Navarro-Arribas, Guillermo; Cavalli, Ana; Leneutre, Jean (Lecture notes in computer science, 2011)
This book constitutes the thoroughly refereed joint post proceedings of two international workshops, the 5th International Workshop on Data Privacy Management, DPM 2010, and the 3rd International Workshop on Autonomous and Spontaneous Security, SETOP 2010, collocated with the ESORICS 2010 symposium in Athens, Greece, in September 2010. The 9 revised full papers for DPM 2010 presented together with two keynote talks are accompanied by 7 revised full papers of SETOP 2010; all papers were carefully reviewed and selected for inclusion in the book. The DPM 2010 papers cover topics such as how to translate the high-level business goals into system-level privacy policies, administration of privacy-sensitive data, privacy data integration and engineering, privacy access control mechanisms, information-oriented security, and query execution on privacy-sensitive data for partial answers. The SETOP 2010 papers address several specific aspects of the previously cited topics, as for instance the autonomic administration of security policies, secure P2P storage, RFID authentication, anonymity in reputation systems, etc.